Rola szkolnego opiekuna praktyk w świetle analizy rozmów pohospitacyjnych z przyszłymi nauczycielami języka francuskiego - Szymankiewicz, Krystyna (Neofilolog, 2023)
The practicum is an important part of the training of prospective foreign language teachers. The reflections proposed in this article deal with the assumptions of mentoring when confronted with its practical implementation, with a particular focus on learning through mentoring dialogues. The text provides an overview of the main models of mentoring in order to show the complexity of the tasks faced by the mentor teacher. Characteristics of the mentoring dialogue are also presented. This theoretical base is referred to in the study, which consisted of a qualitative analysis of mentoring dialogues and comments made afterwards by prospective teachers of French as a foreign language. The aim of the study was to identify the supervisory style, dialogue activity and mentoring roles performed by the mentor teachers. The analysis was also intended to show what kind of mentoring behavior is expected by the pre-service students. The findings show that the majority of mentor teachers dominate the conversation and prefer a directive supervisory style, which seems to meet the trainees’ expectations and needs. The pre-service students emphasize the importance of mentoring dialogues as a learning opportunity, and appreciate constructive criticism, positive reinforcement and concrete guidance on how to teach. The implication of the findings is discussed at the end.